Rapid assessment of multiaxial fatigue lifetime in notched components using an averaged strain energy density approach. (July 2019) - Branco, R.; Prates, P.A.; Costa, J.D.; Borrego, L.P.; Berto, F.; Kotousov, A.; Antunes, F.V.
Highlights: Rapid assessment of fatigue crack initiation lifetime in multiaxially notched components. Failure of notched samples defined via a critical value of the strain energy density at the initiation sites. Rapid evaluation of strain energy density at the initiation site via a computational elastic-plastic framework. Reduced number of cyclic fatigue properties evaluated from two strain-controlled low-cycle fatigue tests. Abstract: This paper proposes a rapid fatigue lifetime assessment approach to deal with notched components undergoing multiaxial loading. The modus operandi consists of calculating an effective quantity of the strain energy density nearby the crack initiation site of the notched component using an elastic-plastic numerical model. This quantity is then inserted into a fatigue master curve connecting the strain energy density with the number of cycles to failure to estimate the number of cycles to fatigue crack initiation. The proposed approach is applied to lateral U-shaped notched round bars subjected to multiaxial in-phase loading histories. Both the experimental results and the numerical predictions are in good agreement.